Cartographies of Violence : Japanese Canadian Women, Memory, and the Subjects of the Internment - Oikawa, Mona, 1955- (Book collections on Project MUSE., 2012)
"In 1942, the federal government expelled more than 22,000 Japanese Canadians from their homes in British Columbia. From 1942 to 1949, they were dispossessed, sent to incarceration sites, and dispersed across Canada. Over 4,000 were deported to Japan. Cartographies of Violence analyses the effects of these processes for some Japanese Canadian women. Using critical race, feminist, anti-colonial, and cultural geographic theory, Mona Oikawa deconstructs prevalent images, stereotypes, and language used to describe the 'internment' in ways that masks its inherent violence. Through interviews with women survivors and their daughters, Oikawa analyses recurring themes of racism and resistance, as well as the struggle to communicate what happened. Disturbing and provocative, Cartographies of Violence explores women's memories in order to map the effects of forced displacements, incarcerations, and the separations of family, friends, and communities"--Publisher's website.